Scientific assessment of agility performance in competitive sports: Evolution, application, reliability, and validity - Ye, J.; Cheng, R.; Gao, B.; Wang, Y.; Wang, Y. (Strength and Conditioning Journal, 2025)
This systematic review aimed to analyze the evolution, reliability, and validity of agility testing in athletes. The results indicated the necessity of prioritizing reactive agility (RA) as the primary focus in the scientific assessment of athletes' agility performance. The cutting and "stop and go" tests were the most widely used agility tests, utilizing light or human random signals as stimuli. Overall, the agility tests demonstrated that high reliability and poor agility performance could be predictive indicators of higher sports injury rates. Convergent validity between the agility and change of direction speed (CODS) tests was moderate. Agility tests could also differentiate athletes with different performance levels and age groups. Future practitioners should focus on customizing the "gold standard" agility tests for specific sports, which includes evaluating the reliability and validity of these tests.